Ideal Identity Construction in Beauty Product Advertisement of Garnier (Universitas Islam Negeri Sunan Ampel Surabaya, 2016)
This study aims at explaining how the advertiser constructs the ideal identity in the Garnier advertisement. It mainly focuses on the characteristics of language and other context used in the advertisement from a Critical Discourse Analysis (CDA) perspective. This is a descriptive qualitative method in which the data were collected from the beauty product advertisements of Garnier. The analysis is based on Fairclough's three dimensional models (textual features, discursive features, and social features). The findings of this study show that the ideal identity in the advertisement of Garnier is constructed by advertiser through the use of textual features and social features. The writer finds out that there is on-going struggle about how the advertisers construct the ideal identity in the modern society by giving the representation of attractive model and how they show their professionalism in technology by giving scientific evidence in their advertisements.